위험 시나리오에 대해 트랜스포머 네트워크 기반 자율주행차량의 충돌 및 궤적 예측 알고리즘 개발 - 이성우; 정영훈; 송봉섭 (한국자동차공학회 논문집, 2024)
This research proposed a method for predicting collisions and trajectories using a transformer network with parallel computing capabilities for multiple vehicles. The accurate prediction of the driving trajectories of surrounding vehicles is essential for the decision-making processes of autonomous vehicles(AVs). Furthermore, the ability to predict imminent collisions can significantly enhance the safety of AVs. However, although several studies have addressed these issues individually, it is rare to find research that tackles both problems simultaneously. Hence, to facilitate the multitasks of collision prediction and trajectory prediction, we modified the prediction head associated with the final layer of the network to enable multitasking capabilities. This study explored two model architectures: one with an encoder-decoder structure and another with only a decoder. The performance of the proposed algorithm is compared with existing algorithms in the literature. The results demonstrate that our suggested algorithm outperforms previous methods in terms of parallelization.
Keywords: 충돌 예측; 궤적 예측; 트랜스포머; 딥러닝; 위험도 평가; 시나리오 기반 평가; Collision prediction; Trajectory prediction; Transformer; Deep learning; Risk assessment; Scenario-based assessment